Improving the effectiveness of anti-texting and driving PSAs: the effect of ad elements on attitude change. Issue 2 (8th March 2021) - Benoit, Ilgım Dara; Miller, Elizabeth G.; Kordrostami, Elika; Ekebas-Turedi, Ceren
Abstract : Purpose: Public service announcements (PSAs) are frequently used tools to try to change attitudes and behaviors on social issues, including texting and driving, which has been social problem for over a decade. However, the effectiveness of such PSA campaigns often meet with varying degrees of success, suggesting changes to current anti-texting and driving campaigns are needed. This study aims to examine how to design more effective anti-texting and driving PSA campaigns by identifying the elements of existing campaigns that have the strongest impact on attitude change. Design/methodology/approach: In total, 682 respondents from Amazon's Mechanical Turk participated in an online study in which they evaluated 162 real-world anti-texting and driving ads. Respondents evaluated the ads on various ad elements (i.e. type of appeal, source of emotion, discrete emotions and perceived creativity), as well as their attitudes toward the issue after seeing the ad. Findings: PSAs that use emotional (vs rational) appeals, evoke emotion through imagery (vs text) and/or use fear (vs disgust, anger or guilt) result in the largest changes in attitude. In addition, more creative PSAs are more effective at changing attitudes. Originality/value: Overall, the results provide useful information to social marketers on how to design more effective anti-texting and driving campaigns.